Efficient floating-point givens rotation unit - Hormigo-Aguilar, Javier; Muñoz, Sergio (Springer, 2020)
High-throughput QR decomposition is a key operation in many advanced signal processing and communication applications. For some of these applications, using floating-point computation is becoming almost compulsory. However, there are scarce works in hardware implementations of floating-point QR decomposition for embedded systems. In this paper, we propose a very efficient high-throughput floating-point Givens rotation unit for QR decomposition. Moreover, the initial proposed design for conventional number formats is enhanced by using the new Half-Unit Biased format. The provided error analysis shows the effectiveness of our proposals and the trade-off of different implementation parameters. We also present FPGA implementation results and a thorough comparison between both approaches. These implementation results also reveal outstanding improvements compared to other previous similar designs in terms of area, latency, and throughput.
This is a post-peer-review, pre-copyedit version of an article published in Circuits, Systems, and Signal Processing.
Keywords: Informática - Aplicaciones; Procesado de señales; Signal processing; Advanced communication; QR Decomposition; Floating-point; HUB format; High-throughput; CORDIC